Insights from cultural anthropology - Kuhn, Karl Allen, 1967- (Insights (Minneapolis, Minn.), 2018)
Each volume in the Insights series discusses: -how this method, approach, or strategy was first developed and how its application has changed over time; -what current questions arise from its use; -what enduring insights it has produced; and -what questions remain for future scholarship. Author Karl Allen Kuhn defines cultural anthropology and shows how viewing the Bible through this lens can be relevant for the study of biblical texts today. He analyzes several specific texts and provides conclusions, challenges, and considerations for the future of cultural anthropology and biblical interpre.